The Narrator’s Silence: Rereading Hosna’s Tragedy In Tayeb Salih’s Season of Migration to the North - Dinurriyah , Itsna Syahadatud (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This paper explores the intersection of silence, complicity, and gendered violence in Tayeb Salih’s Season of Migration to the North, focusing on the narrator’s role in the tragic fate of Hosna Bint Mahmoud. While the narrator is often positioned as a reflective observer, his silence and inaction, in the case of Hosna Bint Mahmoud’s forced marriage and tragic death, expose a deeper moral paralysis shaped by colonial epistemologies and masculine complicity. His responsibility for Mustafa Saeed’s, Hosna’s late husband's, children is also a critical narrative of the Islamic perspective on orphans’ wealth. This study argues that the narrator’s Western education and internalized colonial values produce a fragmented identity, leaving him unable to challenge local gendered violence or resist the patriarchal norms he critiques. The novel ultimately critiques both colonial modernity and patriarchal tradition, calling for a decolonial, feminist consciousness that centers ethical responsibility and gender justice, and applies Islamic rules.